2009
DOI: 10.1002/ajmg.a.32890
|View full text |Cite
|
Sign up to set email alerts
|

Al‐Awadi/Raas‐Rothschild/Schinzel (AARRS) phocomelia syndrome: Case report and developmental field analysis

Abstract: We describe a girl infant with anomalies of the left pelvis and lower limb (pelvic, femoral, and tibial hypogenesis with absent fibula), subtle facial changes, patent foraman ovale, single umbilical artery, single kidney, and imperforate anus. The external genitalia were asymmetric and ambiguous with normal uterus and ovaries visualized by ultrasound. The anomalies are compatible with previously reported cases of Al-Awadi/Raas-Rothschild/Schinzel (AARRS) phocomelia, an autosomal recessive disorder with WNT7 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The case of Subhani et al [2009] is strictly confined to one segment (lower left) with three normal limbs, and thus does not fit diagnostic criteria for AARRS, unless one postulates a somatic mosaic (but no molecular studies were reported); a disruption might be an alternative explanation for the findings in that case.…”
Section: Discussion Nosological Status and Diagnostic Features Of Thementioning
confidence: 96%
“…The case of Subhani et al [2009] is strictly confined to one segment (lower left) with three normal limbs, and thus does not fit diagnostic criteria for AARRS, unless one postulates a somatic mosaic (but no molecular studies were reported); a disruption might be an alternative explanation for the findings in that case.…”
Section: Discussion Nosological Status and Diagnostic Features Of Thementioning
confidence: 96%
“…The sib fetuses described by Lonardo et al [2007] had marked disproportion between a large head and short trunk and spine with marked hygroma and neck hyperextension, and long bone hypoplasia or aplasia with clearly discernible toes; they most probably had a different disorder (and indeed no WNT7A mutations were identified in the family; see below). The case of Subhani et al [2009] is strictly confined to one segment (lower left) with three normal limbs, and thus does not fit diagnostic criteria for AARRS, unless one postulates a somatic mosaic (but no molecular studies were reported); a disruption might be an alternative explanation for the findings in that case.…”
Section: Discussionmentioning
confidence: 99%
“…14 Apart from this, substance abuse, such as cocaine or alcohol, gestational diabetes, and X-ray radiation exposure during pregnancy can lead to phocomelia. 15,16 Antenatal care should be attended as per WHO protocol so that early in utero identification and possible termination of pregnancies with lethal congenital anomalies can be done. Prenatal diagnosis has been reported as early as 11 weeks of gestation in a high-risk pregnancy with fusion abnormalities of both upper and lower extremities and a large cystic hygroma over the lower back.…”
Section: Discussionmentioning
confidence: 99%